Analisis Pengetahuan Siswa dalam Pembelajaran Permainan Bola Besar Penjas di Masa Pandemi - Juang Pahala; Rhama Nurwansyah; Irfan Zinat Achmad (Peneliti.net, 2022)
The purpose of this study was to determine the knowledge of students in the big ball game, which was measured based on five factors, understanding the big ball game, basic techniques, big ball game rules, big ball organization, field size. The sample used in this study were students of SMKN 1 Leuwiliang with a total of 85 people. The data collection technique used in this study is a quantitative descriptive technique. The method used is a survey, data collection techniques using a questionnaire in the form of a guttman scale. The results showed that the analysis of student knowledge in the big ball game stated that it was in the